2010
DOI: 10.1007/s10461-009-9659-2
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Perpetration and Condom Use-Related Factors: Associations with Heterosexual Men’s Consistent Condom Use

Abstract: Intimate partner violence victimization has been linked to sexual HIV risk behavior among heterosexual women. The unique role of perpetration of intimate partner violence (IPV) in sexual risk behavior among men has not been studied as well. Based on interviews with 518 heterosexual men recruited via street-intercept between 2005 and 2007 in New York City, we assessed the relationship between perpetration of IPV against a main female partner and inconsistent condom use with that same partner, while controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 32 publications
5
38
0
1
Order By: Relevance
“…Among heterosexual couples, IPV has been linked to HIV/sexually transmitted infections (STIs) as well as the increased sexual risk behaviors [2][3][4][5], such as unprotected intercourse. Decker et al [6] reported that IPV increased married women's STI symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Among heterosexual couples, IPV has been linked to HIV/sexually transmitted infections (STIs) as well as the increased sexual risk behaviors [2][3][4][5], such as unprotected intercourse. Decker et al [6] reported that IPV increased married women's STI symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…6 The relationship between abuse and HIV infection has been explained by both biological and sociocultural factors. 9,10 For example, studies show that women with a history of adulthood abuse victimization [also known as intimate partner violence (IPV)] are more likely to engage in high-risk behaviors for HIV-infection such as unprotected sex, sex with multiple partners, [11][12][13] and injection drug use (IDU). 14 In developed countries, the prevalence of past childhood sexual abuse is higher among HIV-infected persons and leads to riskier sexual behaviors later in life.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence indicating that physically abusive men engage in riskier sexual behavior than their nonviolent counterparts, including having multiple sexual partners. 9,10 Such behavior may lead to abusive men contracting HIV and passing it onto their female partners through IPSV. Thus, the substantial population-level risk for the transmission of HIV through the pathway of men's violence against women is due to IPSV (as compared with rape outside of the context of an intimate relationship) because a perpetrator, if infected, exposes his partner to HIV many times over the course of a relationship, increasing the likelihood of infection.…”
mentioning
confidence: 99%